Curricular Update of the Study Plan of the Industrial Engineering Program of the Tunja Sectional Santo Tomás University (LACCEI, 2024)
Industrial engineering is a discipline that focuses on the optimization of systems and processes. Among the competencies that industrial engineering graduates are expected to develop are the ability to analyze and design systems, human and material resource management, production planning and control, quality management, and decision-making. However, the industry and the job market are constantly evolving. Changes in technology, globalization, and competition force companies to continually adapt and reinvent themselves. In this sense, it is essential that study plans in industrial engineering are constantly updated to meet the needs of the market. The improvement of the curriculum in industrial engineering must be approached from different perspectives. Below are some of the areas to consider when updating the curriculum. Generic and specific skills are essential for the training of an industrial engineer. Generic competencies include communication skills, teamwork, leadership, ethics, and social responsibility, while specific competencies include technical skills in areas such as process engineering, production planning, and quality management. Technology is constantly evolving, and it is essential that industrial engineering curricula be updated to include the latest technological trends. Areas to consider include artificial intelligence, robotics, automation, and data management. Practical experience is essential for industrial engineering students to apply the concepts and skills learned in the classroom to real situations. Internships, company visits, and research projects are some of the ways students can be given the practical experience they need. Internationalization is increasingly important in the world of work. Curricula in industrial engineering must include elements that allow students to develop skills in an international environment, such as language learning and the possibility of academic exchanges. Improving the industrial engineering curriculum is essential to ensure that graduates have the necessary skills and competencies to face the challenges of the labor market. Updating in technology, the inclusion of generic and specific skills, practical experience and internationalization are some of the areas that should be considered when updating the curiculum.